A new chart based on sample variances for monitoring the covariance matrix of multivariate processes - Costa, A. F. B. [UNESP]; Machado, M. A. G. [UNESP] (Springer London Ltd, 2009)
In this article, we propose a control chart for detecting shifts in the covariance matrix of a multivariate process. The monitoring statistic is based on the standardized sample variance of p quality characteristics we call the VMAX statistic. The points plotted on the chart correspond to the maximum of the values of these p variances. The reasons to consider the VMAX statistic instead of the generalized variance |S| are faster detection of process changes and better diagnostic features, which mean that the VMAX statistic is better at identifying the out-of-control variable. User's familiarity with sample variances is another point in favor of the VMAX statistic. An example is presented to illustrate the application of the proposed chart.
Keywords: Control charts; Multivariate processes; Covariance matrix; Generalized variance